Mechanism of Mongolian Medicine Eerdun Wurile in Improving Postoperative Cognitive Dysfunction Through Activation of the PI3K Signaling Pathway - Lv, Zhixin; Che, Limuge; Du, Yiri; Yu, Jianshe; Su, Enboer; Liu, Hui; Chen, Dongmei (Frontiers in Neuroscience, 2022)
Objective: By producing an animal model of post-operative cognitive dysfunction (POCD), we explored whether Eerdun wurile, a traditional Mongolian Medicine, could affect the cognitive function of rats by activating the IRS-PI3K-AKT-GLUT4 pathway.Methods: Fifty clean grade adult SD male rats were randomly assigned to one of five groups:1. A control group (Group C) 2.A POCD model group (Group P)3. POCD group with low dose treatment with Erdun wurile. (Group L) 4.A POCD group with high-dose treatment (Group H), and 5. A positive control group (Group D). Trials started 7 days after all rats had acclimated to housing. The rats were trained in water maze location navigation starting 5 days before surgery.All rats underwent the Morris water maze navigation localization and spatial exploration experiments on the preoperative day 1 and postoperative days 1, 3, 5, and their learning and memory abilities were assessed.At the end of the water maze experiment, the rats were sacrificed to obtain hippocampal tissue.The mRNA levels of IRS-2, PI3K, AKT, and GLUT4 were measured in the hippocampus by real-time PCR and the expression of IRS-2, PI3K, AKT and GLUT4 protein in hippocampus was determined by Western blot.Conclusion The Mongolian medicine Eerdun wurile can decrease the occurrence of postoperative cognitive dysfunction in rats. The mechanism may be related to insulin downstream signal molecule PI3K and IRS-PI3K-AKT-GLUT4 signaling pathway.